The Role of Intellectual Capital and Good Corporate Governance on Financial Performance (Empirical Study on Food and Beverage Subsector Manufacturing Sector Companies listed on the IDX 2019-2022) - Indah Febriani; Ratna Linar Sumiartini; Siti Nur Hadiyati (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to analyze and obtain empirically the influence of Intellectual Capital (IC) and Good Corporate Governance (GCG) including institutional ownership, audit committee, and board of commissioners on financial performance as measured using Net Profit Margin (NPM) and Return on Asset (ROA). The population used is food and beverage subsector manufacturing companies listed on the IDX in 2019-2022. This research also uses a type of quantitative research with a multiple linear regression analysis system. The results revealed that (1) Intellectual Capital (IC) has no influence on financial performance as measured using NPM and has a significant positive influence when measured using ROA; (2) The proportion of institutional ownership has no influence on financial performance as measured using NPM and has a significant posisive influence when measured using ROA; (3) The proportion of the audit committee has a significant positive influence on financial performance as measured using NPM and has no influence on ROA; (4) The board of commissioners has a significant positive influence on financial performance as measured using NPM and has no influence when measured using ROA.